(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This study compares task-based language teaching (TBLT) with traditional grammar-translation methods in the context of an English as a Foreign Language (EFL) university in Uzbekistan. Using a quasi-experimental design with 110 undergraduate students over 16 weeks, the study examines learning outcomes in terms of language skills, motivation, and implementation difficulties. However, traditional teaching shows an initial advantage in discrete grammar knowledge, but this difference decreases over time. Qualitative findings reveal implementation difficulties such as the complexity of task design, time management, and students’ resistance to unfamiliar methods. The study provides empirical evidence supporting the effectiveness of TBLT and provides practical recommendations for teachers moving from traditional approaches to task-based approaches in EFL contexts.